Close Interpersonal Relations with Parents and Peers in Adolescence as the Factor of Use of Moral Disengagement Mechanisms - Molchanov S.V.; Almazova O.V. (Психолого-педагогические исследования, 2020)
The aim of the study was to investigate the link between the characteristics of close interpersonal relationships of adolescents in the family and with peers and the preferred mechanisms of moral self-justification. The data consists of 411 adolescences aged from 15 to 17 (Me=15,7; SD=0,7), 278 (67,6%) are men and 133 (32,4%) are women. 3 questionnaires were used: the adapted in Russian moral disengagement questionnaire by C. Moore, the questionnaire of attachment to mother in adolescence. By M. Yaremchuk, the questionnaire of attachment to parents and peers (the form about peers attachment) by G. Armsden and M. Greenberg). Results allowed to define preferred moral disengagement mechanisms. Three strategies of moral freedom were defined: active users, passive users and strategy focused on distortion of victim image. Identified moral freedom strategies are linked with the attachment to the mother and close relations with peers. Adolescents with secure mother attachment and trust, success in communication with peers are less active use moral disengagement mechanisms. Rejection, low trust level and low success in communication correlates with active use of moral disengagement mechanisms.